Implementation of the Montessori Method in Early Childhood Education: A Case Study on Early Childhood Education Institutions Applying the Montessori Method - Nur Fadillah, Ega; Daffa, Muhammad Yusuf (Sekolah Tinggi Agama Islam Kuningan, 2024)
Backround: The Montessori method offers an innovative approach to early childhood education, but its implementation in Indonesia faces various challenges.Objective: This study examines the effectiveness and implementation of the Montessori method in Indonesian PAUD institutions using a mixed-method approach with a sequential explanatory design. The research was carried out in 5 Montessori PAUD institutions in Jakarta, Bandung, and Yogyakarta (January-June 2024).Method: The quantitative component involved 120 children aged 3-6 years with pre-test and post-test using ASQ-3, Child Development Inventory, Montessori Assessment Checklist, SSRS, and DESSA-mini, analyzed by paired sample t-test and ANOVA. The qualitative component included structured observation (600 hours), in-depth interviews with 25 teachers and 5 principals, and focus group discussions with 100 parents, analyzed using thematic analysis.Findings and Implications: Quantitative results showed a significant increase (p<0.001): independence 42.7% (Cohen’s d=1.87), cognitive 38.5%, and social-emotional 44.3%. The quality of the prepared environment is strongly correlated with developmental outcomes (r=0.78). The qualitative analysis identified five themes: prepared environment as a foundation, transformation of the role of teachers into observer-facilitators (68% of the time for observation), practical life activities as the key to independence, mixed-age grouping facilitating peer learning, and implementation challenges including the scarcity of trained teachers (68%), high material costs (76%), and parental misconceptions (58%).Conclusion: The Montessori method is effective in optimizing the holistic development of children when implemented with high fidelity. Government policies are needed for certification recognition, material subsidies, development of local production, and systematic parent education to expand access to quality Montessori education.